Komitmen Pegawai dan Budaya Organisasi pada Kinerja Pegawai - Gatot Wijayanto (JIANA ( Jurnal Ilmu Administrasi Negara ), 2011)
This study aims to analyze and examine the influence of commitment employee andcultural organizational factors towards employees of the Job Performance, Sekretariat Daerah (SetDa)Riau Province both simultaneously (overall test) and partial (individual test). Research methodused is verifikatif, while the population in this study are the Sekretariat Daerah (SetDa) RiauProvince based on esselonering totaling 402 people. By using the method of proportional stratifiedrandom sampling in the sample amounted to obtain 40 respondents. While data collection tech-niques used by the field study and library that includes observation, interviews and question-naires, and to determine the relationship and the influence of an independent variable to the modelvariables to use Multiple Linear Regression Analysis. The results showed that the calculationresults obtained statistically Multiple Correlation Coefficient (R) is 0.8950 with p <0.05 and thecoefficient value of Determination (R2) 80.11%. This means that approximately 80.11% factor ofemployee commitment and organizational culture have a significant influence on employee job,performance. Partial test showed that the partial coefficient of determination values contained inthe organizational culture variables for (r2) = 54.58% with p = 0.00000 and tresult = 7.515> ttable = 1.678and ttabel variables for employee commitment (r2) = 78, 74% with p = 0.00000 and tresult = 13.196> ttable= 1.678. These results indicate that organizational cultural factors and commitment employees havea relationship significant influence on employee job performance Sekretariat Daerah (SetDa) RiauProvince.